2017
DOI: 10.1371/journal.pone.0176056
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of the isocitrate dehydrogenase with dual coenzyme specificity from the obligate methylotroph Methylobacillus Flagellatus

Abstract: The isocitrate dehydrogenase (MfIDH) with unique double coenzyme specificity from Methylobacillus flagellatus was purified and characterized, and its gene was cloned and overexpressed in E. coli as a fused protein. This enzyme is homodimeric,—with a subunit molecular mass of 45 kDa and a specific activity of 182 U mg -1 with NAD+ and 63 U mg -1 with NADP+. The MfIDH activity was dependent on divalent cations and Mn2+ enhanced the activity the most effectively. MfIDH exhibited a cofactor-dependent pH-activity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…This resulted in 125 studies being excluded. The remaining 89 studies were included for meta-analysis, of which 63 studies with CIN 1 patients, 8–70 42 studies with CIN 2 patients, 11,26,27,35–37,39,41–44,50,52,53,57,69–95 and 7 studies with CIN 3 patients 3,26,41,72,81,83,88 . The characteristics and the follow-up protocol of the included studies are summarized in Supplementary Tables 1–3, http://links.lww.com/LGT/A239, http://links.lww.com/LGT/A240, http://links.lww.com/LGT/A241.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in 125 studies being excluded. The remaining 89 studies were included for meta-analysis, of which 63 studies with CIN 1 patients, 8–70 42 studies with CIN 2 patients, 11,26,27,35–37,39,41–44,50,52,53,57,69–95 and 7 studies with CIN 3 patients 3,26,41,72,81,83,88 . The characteristics and the follow-up protocol of the included studies are summarized in Supplementary Tables 1–3, http://links.lww.com/LGT/A239, http://links.lww.com/LGT/A240, http://links.lww.com/LGT/A241.…”
Section: Resultsmentioning
confidence: 99%
“…High risk of bias was in most studies caused by the unrepresentativeness of the cohort for the full population in a predefined period [11][12][13]24,27,28,30,[32][33][34]36,37,40,[42][43][44]48,50,51,53,57,59,61,71,[73][74][75][76][77]79,[83][84][85][86][87][88][91][92][93]95 and the low number of participants in the study. 8,9,11,12,26,27,34,36,37,39,[42]…”
Section: Risk Of Biasmentioning
confidence: 99%
“…In this study, low concentrations of Fe 3+ (0.1 ± 0.1 mg/L in system E) enhanced the microbial metabolic activity and promoted the degradation of pollutants. Mn 2+ was most effective in enhancing the enzyme activity of Methylophilaceae than Mg 2+ and Zn 2+ . What’s more, Cu 2+ played a key role in the physiology and activity of MOB because it acts as the metal center for the particulate methane monooxygenase of MOB …”
Section: Resultsmentioning
confidence: 99%
“…Mn 2+ was most effective in enhancing the enzyme activity of Methylophilaceae than Mg 2+ and Zn 2+ . 38 What's more, Cu 2+ played a key role in the physiology and activity of MOB because it acts as the metal center for the particulate methane monooxygenase of MOB. 39 Synergistic removal of nutrient pollutants and PPCPs from contaminated groundwater was achieved in system E; the removal efficiencies of nutrient pollutants were 75.8 ± 20.1%− 94.3 ± 8.8%, which were approximately 29.5 ± 9.8%−39.4 ± 5.4% higher than for the other four systems.…”
Section: Methodsmentioning
confidence: 99%
“…Romkina and Kiriukhin (2017) previously reported that the decrease in NAD + at 340nm was used to evaluate isocitrate dehydrogenase (IDH) activity. 15…”
Section: Determination Of Hepatic Isocitrate Dehydrogenase Activitymentioning
confidence: 99%